150 new students receive UMPSA Excellence Incentive - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
GAMBANG, 29 September 2024 – A total of 150 outstanding students, who have completed their diplomas, matriculation, polytechnic, Vocational College, or the Malaysian Higher School Certificate (STPM), and were selected to pursue their studies at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), have been awarded the UMPSA Foundation Excellence Incentive for this academic session.